2004
DOI: 10.1111/j.1087-0024.2004.09309.x
|View full text |Cite
|
Sign up to set email alerts
|

As Epidermal Stem Cells Age they do not Substantially Change their Characteristics

Abstract: In this study, we ask the basic question: do stem cells age? We demonstrated that epidermal stem cells isolated from neonatal mice had the capacity to form multiple cell lineages during development. Here we demonstrate the cell lineages are clonal, and that epidermal stem cells isolated from the footpad epithelium of old mice have similar capabilities. Using Hoechst dye exclusion and cell size, we isolated viable homogenous populations of epidermal stem and transit-amplifying (TA) cells from GFP-transgenic mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 62 publications
0
33
0
1
Order By: Relevance
“…The sorting method used was a significant refinement of one we have previously published (Liang & Bickenbach, 2002;Liang et al ., 2004). This technique was based on two observations: (i) somatic stem cell populations were able to actively exclude the vital dye Hoechst 33342, an ability mediated by the expression of the Abcg2 transporter (Goodell et al ., 1996;Zhou et al ., 2001), and (ii) the smallest epidermal keratinocytes had been shown to have the largest clonogenic potential in vitro (Barrandon & Green, 1985).…”
Section: The Percentage Of Murine Episcs Does Not Change With Agementioning
confidence: 99%
See 1 more Smart Citation
“…The sorting method used was a significant refinement of one we have previously published (Liang & Bickenbach, 2002;Liang et al ., 2004). This technique was based on two observations: (i) somatic stem cell populations were able to actively exclude the vital dye Hoechst 33342, an ability mediated by the expression of the Abcg2 transporter (Goodell et al ., 1996;Zhou et al ., 2001), and (ii) the smallest epidermal keratinocytes had been shown to have the largest clonogenic potential in vitro (Barrandon & Green, 1985).…”
Section: The Percentage Of Murine Episcs Does Not Change With Agementioning
confidence: 99%
“…Thus, it is imperative that any study of somatic stem cells test this property. Because the EpiSC sorting method that we used here was modified to collect a subset of the cells that we had previously reported as multipotent (Liang & Bickenbach, 2002;Liang et al, 2004), we wanted to ensure that these EpiSCs also showed this capability. Using the same protocol, EpiSCs and TA cells were isolated from 22-month-old transgenic mice that ubiquitously expressed GFP.…”
Section: Episcs Maintain Multipotent Capability Into Old Agementioning
confidence: 99%
“…cell compartment has not revealed senescent epidermal stem cells even though their transiently amplifying progeny may undergo senescence (Liang et al, 2004;Stern and Bickenbach, 2007;Giangreco et al, 2008;Charruyer et al, 2009).…”
Section: Ink4amentioning
confidence: 99%
“…However, work from our lab and others suggests that this is not the case for all somatic stem cells, that mammalian epidermal stem cells appear to resist the aging process. These adult stem cells show no loss in numbers, no changes in gene expression or cellular function, and no changes in telomere length with respect to age [6-8]. …”
Section: Why Epidermal Stem Cells Might Be Unique mentioning
confidence: 99%
“…The second method showed that the smallest epidermal keratinocytes were the cells that produced the largest clonogenic potential in vitro [23]. Epidermal cells, isolated by combining these two methods, not only recapitulate a functional epidermis, but also show multipotency when injected into a developing mouse blastocyst [6,16]. This is irrespective of the cell's age.…”
Section: Epidermal Stem Cells Remain Undimentioning
confidence: 99%